Estudio del comportamiento del consumidor de comercio electrónico y su grado de satisfacción en las compras online - Ramirez Ramirez, Dannyel Jazmany (2015)
In the present world, thanks to globalization and technology people are going to evolve the same way to buy, we want to make purchases in a way easier from the comfort of our home or where we will be in any part of the world. Thanks to the internet it is possible to make on-line purchases, in our country, as well as in the city Machala this form of buy is increasing every day more people are becoming consumers online hence the importance of our research to determine and identify the behavior of the e-consumer through a field research that allows us to identify patterns of consumption, how the people who make purchases on the internet. The data obtained in the research enable you to implement marketing strategies more effective, once identified the segment on which we are going to direct. The results obtained in our field investigation, people prefer to buy on the internet due to its ease and primary product in technology, primarily in the masculine gender young people who enjoy the new trends, women in the same way young people on the other hand, its main attraction of online purchases are for personal use which are attracted by the tenders that these shops offered and the ease of borrowing from credit cards. In the city of Machala even the majority of internet users do not make purchases online you have afraid to give personal information or be deceived, hence the importance that the companies dedicated to online sales of our country should be promoted and make themselves known to provide the client greater security and guarantee their purchase.